2021
DOI: 10.30998/sosioekons.v13i2.9749
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh kepuasan kerja dan komitmen organisasi terhadap organizational citizenship behavior karyawan

Abstract: Organizational Citizenship Behavior is currently a concern of organizational leaders around the world. This study aims to determine the effect of job satisfaction and organizational commitment to Organizational Citizenship Behavior partially and simultaneously. The research method used is quantitative research with survey methods. The sampling technique is a saturated sample that uses the entire population of employees in the Blood Transfusion Unit of the Indonesian Red Cross Center of 78 people. Data collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
2
1
0
1
Order By: Relevance
“…Employee job satisfaction can increase high morale, making them willing to help colleagues who are unable to attend, help colleagues who need assistance, always be active and participate in office activities, and always attend office meetings. It is in line with several studies (Deskriyanto & Ratnaningrum, 2021;Ismaillah & Prasetyono, 2021;Kurniawan et al, 2021;Nefianasari, 2021;Nurhayati et al, 2016;Prameswari & Suwandana, 2017;Siswanto et al, 2021;Sumijan, 2021;Yulianto, 2021) which showed that job satisfaction significantly has positive effects on OCB.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Employee job satisfaction can increase high morale, making them willing to help colleagues who are unable to attend, help colleagues who need assistance, always be active and participate in office activities, and always attend office meetings. It is in line with several studies (Deskriyanto & Ratnaningrum, 2021;Ismaillah & Prasetyono, 2021;Kurniawan et al, 2021;Nefianasari, 2021;Nurhayati et al, 2016;Prameswari & Suwandana, 2017;Siswanto et al, 2021;Sumijan, 2021;Yulianto, 2021) which showed that job satisfaction significantly has positive effects on OCB.…”
Section: Discussionsupporting
confidence: 89%
“…Some problems or challenges might not be tough to do. Previous studies indicated that job satisfaction significantly has a positive effect on OCB (Ismaillah & Prasetyono, 2021). It means that great job satisfaction will increase employees' Organizational Citizenship Behaviour.…”
Section: Job Satisfaction and Organizational Citizenship Behaviormentioning
confidence: 95%
“…Gunawan's (2019) research on 91 vocational school teachers in Brebes stated that the higher the job satisfaction, the higher the organizational citizenship behavior. The research results reinforce this by Ismaillah & Prasetyono (2021), which state that job satisfaction partially has a positive and significant effect on OCB. Likewise, the research of Titin et al ( 2021) says that job characteristics, quality of work-life and job satisfaction have a significant and simultaneous effect on OCB.…”
Section: Indirect Influencesupporting
confidence: 79%
“…Servant dan meningkatkan efektivitas organisasi secara keseluruhan (Ismaillah and Prasetyono, 2021).…”
Section: Servant Leadershipunclassified